Effectiveness of Two Different Methods for Pain Reduction During Insulin Injection in Children With Type 1 Diabetes: Buzzy and ShotBlocker. Issue 6 (11th October 2018) - Canbulat Sahiner, Nejla; Turkmen, Ayse Sonay; Acikgoz, Ayfer; Simsek, Enver; Kirel, Birgul
Abstract: Background: Repeated injections may prevent children from performing insulin administration (skip dosing) and may cause anxiety. Aims: To compare the effect of ShotBlocker and the combination of vibration and cold application (Buzzy) in reducing pain during insulin administration in children. Methods: This research was designed as a randomized controlled experimental study. The study sample consisted of 60 children aged between 6 and 12 years who were diagnosed as having type 1 diabetes and received insulin from the Child Endocrinology Department of the medical faculty in Eskisehir Osmangazi University between May 2015 and June 2017. The children were randomized into the Buzzy ( n  =   20), ShotBlocker ( n  =   20), and control ( n  =   20) groups. Three instruments were used to obtain the research data: Interview and Observation Form, Children's Anxiety and Pain Scale (CAPS), and Faces Pain Scale—Revised (FPS‐R). Results: The mean age of the children was 9.43 ± 2.18 years (range 6–12 years). There were no significant differences among preprocedural anxiety levels of the study groups in terms of self‐, parent‐, and observer‐reported levels ( p  =   .935, p  =   .374, and p  =   .680, respectively). Children in the control group had higher levels of pain than children in the Buzzy and ShotBlocker groups ( p  =   .008, p  =   .007, and p  >   .001, respectively). There was a significant difference between the groups with procedural anxiety levels reported by the family and observer ( p  =   .006 and p  =   .002, respectively), favoring the intervention groups. Linking Evidence to Action: Nurses should be aware of pain during insulin injection and use methods for pain relief accordingly. ShotBlocker is recommended as a helpful option in cases where a pain control method is required.